Immunohistopathological characterization and the impact of topical immunomodulatory therapy in oral chronic graft‐versus‐host disease: A pilot study. (13th March 2018) - Motta, ACF; Zhan, Q; Larson, A; Lerman, M; Woo, S‐B; Soiffer, RJ; Murphy, GF; Treister, NS
Abstract : Objective: To characterize the immunohistopathological features of oral chronic graft‐versus‐host disease (cGVHD), and the impact of topical immunomodulatory therapy on the infiltrating cells. Material and Methods: Paired oral cGVHD biopsies obtained before ( n  = 12) and 1 month after treatment ( n  = 12) with topical dexamethasone ( n  = 8) or tacrolimus ( n  = 4) were characterized by immunohistochemistry using a panel of CD1a, CD3, CD4, CD8, CD20, CD31, CD62E, CD103, CD163, c‐kit, and FoxP3. Controls included acute GVHD (aGVHD; n  = 3), oral lichen planus (OLP; n  = 5), and normal tissues ( n  = 5). Results: Oral cGVHD specimens prior to treatment were mainly characterized by basal cell squamatization, lichenoid inflammation, sclerosis, apoptosis, and lymphocytic exocytosis. The infiltrating cells in oral cGVHD primarily consisted of CD3 +, CD4 +, CD8 +, CD103 +, CD163 +, and FoxP3 + cells, which were higher than in normal tissues. Topical dexamethasone or tacrolimus reduced neutrophilic exocytosis, basal cell squamatization, and lichenoid inflammation in oral cGVHD, and dexamethasone reduced the number of CD4 + and CD103 + cells. Conclusion: The high expression of CD3, CD4, CD8, CD103, CD163, and FoxP3 confirms that oral cGVHD is largely T‐cell‐driven with macrophage participation. The impact of topical immunomodulatory therapy was variable, reducing histological inflammatory features, but with a weak clinicopathological correlation. Topical dexamethasone reduced the expression of CD4 and CD103, which may offer novel therapeutic targets.